"Here be dragons!" The gross under‐representation of the Global South on editorial boards in Geography. Issue 4 (17th August 2021) - Hedding, David William; Breetzke, Gregory
Abstract: One manifestation of the glaring lack of equality, diversity, and inclusion in higher education relates to the underrepresentation of certain individuals and/or regions in the scholarly publication process. Here, we analyse the affiliations of editorial board members in 126 Geography journals. Specifically, we examine editorial board membership by region and determine the extent to which the regional representation of editorial board members is associated with journal impact factor as a measure of journal reach and quality. Of the 5, 202 editorial board members examined, almost 80% are located in mainland Europe, North America, and the British Isles, while roughly five percent are located in Central America, South America, the Middle East, and Africa combined. Moreover, editorial board members located in these four regions from the Global South are most often editorial board members of journals in the lowest quartile (by impact factor). These findings highlight the outdated and exclusionary practices that pervade the scholarly publication process in science in general, and Geography specifically. Abstract : One manifestation of the glaring lack of equality, diversity, and inclusion in higher education relates to the underrepresentation of certain individuals and/or regions in the scholarly publication process. Here, we analyse the affiliations of editorial board members in 126 Geography journals. Of the 5, 202 editorial board members examined, almost 80% are located in Mainland Europe, North America, and the British Isles while roughly five percent are located in Central America, South America, the Middle East, and Africa combined.